1990
DOI: 10.1152/jappl.1990.69.2.597
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ischemia reperfusion or hypoxia reoxygenation on lung vascular permeability and resistance

Abstract: The effect of ischemia reperfusion or hypoxia reoxygenation on pulmonary vascular permeability and resistance was studied in 25 isolated blood-perfused dog lungs. Vascular permeability, assessed by determining filtration coefficient (Kf), and vascular resistances were measured at the beginning and end of the experiment. Ischemia reperfusion was produced by occluding blood flow to the lung for 3 h and reperfusing for 1 h, whereas hypoxia reoxygenation was obtained by ventilating the lung with 95% N2-5% CO2 for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(32 citation statements)
references
References 0 publications
0
31
0
1
Order By: Relevance
“…The increase in PVR is mainly due to the vasoconstriction of the pulmonary precapillary system after lung IR (120). The increase in PVR, together with an increase of vascular permeability, the latter of lesser importance (11), results in pulmonary edema in both ischemia (23) and reperfusion (93). The increase in total and extravascular lung water content causes poor gas exchange and lung mechanics, which leads to a lower arterial oxygen tension (Pa O 2 ) (93), increased peak airway pressure, and an elevated alveolar-arterial oxygen gradient [(A-a)DO 2 ] (166).…”
Section: Ir-induced Physiological Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in PVR is mainly due to the vasoconstriction of the pulmonary precapillary system after lung IR (120). The increase in PVR, together with an increase of vascular permeability, the latter of lesser importance (11), results in pulmonary edema in both ischemia (23) and reperfusion (93). The increase in total and extravascular lung water content causes poor gas exchange and lung mechanics, which leads to a lower arterial oxygen tension (Pa O 2 ) (93), increased peak airway pressure, and an elevated alveolar-arterial oxygen gradient [(A-a)DO 2 ] (166).…”
Section: Ir-induced Physiological Changesmentioning
confidence: 99%
“…However, the depletion of lung oxygenation by stopping the ventilation leads to the same degree of lung impairment as a decrease in mechanotransduction by loss of blood flow, as determined by increases in vascular pressure and permeability (11), indicating that any deficiency from oxygenation or mechanotransduction can have significant repercussions (149).…”
mentioning
confidence: 99%
“…Allopurinol is another XOD inhibitor that often has been used to study the enzyme's function and has been shown to effectively attenuate lung reoxygenation injury (1,34,35). However, it has also been shown that oxypurinol, a major metabolite of allopurinol, is a scavenger of the highly reactive hydroxyl radical and of hypochlorous acid.…”
Section: Discussionmentioning
confidence: 99%
“…This type of injury also occurs in lungs (7-1 1). For volume technique, averaged 0.591 f 0.054 (SEM) and example, Allison et al (12) recently demonstrated that ventila-0.465 f 0.054 (SEM), respectively, and were not altered tion of isolated perfused dog lungs with 95% N2/5% C 0 2 followed by reoxygenation or age. Catalase activity in lung tissue by 95% 0215% COz increased pulmonary vascular resistance and erythrocytes was lower in premature lambs, but there and filtration coefficient.…”
mentioning
confidence: 99%